IDDF2019-ABS-0138 Changes in oro-cecal transit time(OCTT) and prevalence of lactose intolerance in patients of microscopic colitis. (7th June 2019) - Bellam, Balaji; Shukla, Siddharth; Kochhar, Rakesh; Singh, Anupam Kumar; Rana, Satyavathi; Prasad, Kaushal K; Malik, Sarthak; Berry, Neha; Sharma, Megha; Sinha, Saroj Kant
Abstract : Background: Microscopic colitis (MC) remains an elusive cause of chronic diarrhea. Histopathology is a gold standard with variable yield. The OCTT and concomitant lactose intolerance in these cases may aid to understand the complex symptoms. We used Hydrogen(H2) breath tests (H2 BT) for detecting SIBO (Small Intestinal Bacterial Overgrowth), Lactose intolerance and calculation of oro-cecal transit time (OCTT). Methods: 43 MC patients [mean age - 45.83(±15.92] and 10 controls were studied. Among these, 37(86%) patients with MC & 9 (90%) controls underwent breath tests. SIBO was diagnosed with glucose H2 BT. For confirmation, we took rise ≥12 ppm over fasting value in H2 concentration within 2hours of glucose ingestion Lactulose H2 BT was done to calculate OCTT. Time taken for rising in breath hydrogen by ≥12ppm over baseline value in two consecutive readings was considered as OCTT. For lactose breath test, 15 minutes samples were taken up to 4 hours. A ≥20 ppm rise over fasting value in H2 concentration in two consecutive readings was considered intolerance Results: Four(9.5%) patients of SIBO in Glucose H2 BT were enrolled in controls. Mean (+ SD) OCTT in cases of MC vs controls was 130.38±47.95 mins and 97.14±48.55 mins (p= 0.109) respectively. Thus OCTT increased in 73% cases of MC vs 43% controls. Also, in the MC group, 9(28.1%) patients were lactose intolerant while vs 3(42.9%) controls (p= 0.654). Thus a significant 28% MC patients were lactose intolerant possibly aggravating symptoms Conclusions: Lactose intolerance has lesser prevalence in cases of microscopic colitis. These patients were also detected to have paradoxically prolonged OCTT excluding the role of small bowel in diarrheal symptoms